2015
DOI: 10.1002/cmdc.201500457
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of JMV4463, a Vectorized Cathepsin D Inhibitor with Antiproliferative Properties: The Unique Role of the AMPA‐Based Vector

Abstract: Cathepsin D (CathD) is overexpressed and secreted by several solid tumors and stimulates their growth, the mechanism of which is still not understood. In this context, the pepstatin bioconjugate JMV4463 [Ac-arg-O2 Oc-(Val)3-Sta-Ala-Sta-(AMPA)4-NH2; O2 Oc=8-amino-3,6-dioxaoctanoyl, Sta=statine, AMPA=ortho-aminomethylphenylacetyl], containing a new kind of cell-penetrating vector, was previously shown to exhibit potent antiproliferative effects in vitro and to delay the onset of tumors in vivo. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Prior studies have noted that Cathepsin D is involved in degradation of extracellular matrix and basement membrane in cancers due to its proteolytic activity [ 29 ]. A study using a vectorized Cathepsin D inhibitor found that anti-proliferative activity was associated with Cathepsin D inhibition, suggesting that intracellular Cathepsin D plays a major role in cancer cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have noted that Cathepsin D is involved in degradation of extracellular matrix and basement membrane in cancers due to its proteolytic activity [ 29 ]. A study using a vectorized Cathepsin D inhibitor found that anti-proliferative activity was associated with Cathepsin D inhibition, suggesting that intracellular Cathepsin D plays a major role in cancer cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This chemically stable conjugate could be efficiently ingested by retinal cells and exhibited cathepsin D-accelerated drug release and targeted therapy for ocular diseases. Another approach focused on the vectorization of cathepsin D inhibitors and the interpretation of their structure-function relevance 286 , 287 . For cathepsin E, recent studies emphasized exploring its feasibility as a molecular target for cancer theranostics and developing its clinical application potency 288 .…”
Section: Protease-responsive Nanodds For the Targeted Theranostics Of Malignancymentioning
confidence: 99%
“…However, the poor intracellular penetration of pepstatin A strictly limited its use on cancer cells. To overcome this drawback, a pepstatin bioconjugation was designed and showed satisfactory results on tumor cells and mice xenografted with breast cancer cells [20,21]. In our efforts to explore cyanobacterial peptides as a source of novel drug candidates [22][23][24][25][26][27][28], we have finished the total synthesis and structural reassignment of tasiamide B [28], which contained a statine-like unit (4-amino-3-hydroxy-5phenylpentanoic acid, Ahppa).…”
Section: Introductionmentioning
confidence: 99%